2018
DOI: 10.3389/fmicb.2018.00064
|View full text |Cite
|
Sign up to set email alerts
|

New Aspects on Listeria monocytogenes ST5-ECVI Predominance in a Heavily Contaminated Cheese Processing Environment

Abstract: The eradication of Listeria monocytogenes from food chains is still a great challenge for the food industry and control authorities since some clonal complexes (CCs) are either better adapted to food processing environments (FPEs) or are globally widespread. In this work, we focus on the in-house evolution of L. monocytogenes genotypes collected from a heavily contaminated FPE whose contamination pattern underwent a massive and yet unexplained change. At the beginning of the sampling in 2010, a high variety of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
40
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 59 publications
9
40
2
Order By: Relevance
“…The stress survival islets (SSI-1 and SSI2) are known to be responsible for the proliferation of L. monocytogenes under stressful conditions in food processing facilities [39,40]. In the current study, SSI-1 was detected in a E313 sample belonging to ST1 of lineage I. SSI-2 was present in two samples (E367 and E362) which belong to ST121 and ST204 of lineage II, respectively (Table 2).…”
Section: Stress Survival Isletsupporting
confidence: 49%
See 2 more Smart Citations
“…The stress survival islets (SSI-1 and SSI2) are known to be responsible for the proliferation of L. monocytogenes under stressful conditions in food processing facilities [39,40]. In the current study, SSI-1 was detected in a E313 sample belonging to ST1 of lineage I. SSI-2 was present in two samples (E367 and E362) which belong to ST121 and ST204 of lineage II, respectively (Table 2).…”
Section: Stress Survival Isletsupporting
confidence: 49%
“…The LIPI4 appears to be strongly associated with ST4 isolates [1]; hence, it was not observed in the current study. Several studies have identified mutations that are important in L. monocytogenes virulence markers [40,[56][57][58]. The analysis of all sequenced strains in the present study indicated that they all encode for full-length InlA and ActA proteins.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Multiple plasmid-borne homologous genes have been recently associated with lineage II food isolates [15]. Without a full description of the causal mechanisms promoting this particular phenotype, strains belonging to food-associated clonal groups of lineage II, including CC121, CC9, CC8, CC101, CC7 and CC204, have been shown to be persistent in FPEs [16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the three-gene cassette bcrABC, located either on the chromosome or transposable units of L. monocytogenes strains, was described as conferring an increased resistance to BC, a widely used QAC disinfectant in the food industry in the past few decades [36]. The bcrABC cassette was detected in L. monocytogenes strains belonging to CC121, CC5, CC9, CC8, CC14 and CC204 [19,21,26] but not to CC7, CC101 and CC155 [18,26]. In addition, the transposon Tn6188 carrying the transporter QacH, and the transposon LGI1, carrying a small multidrug-resistant (SMR) efflux pump encoded by emrE, both responsible for enhanced BC tolerance, have been described as specific to CC121 and CC8 strains, respectively [35,37,38].…”
Section: Introductionmentioning
confidence: 99%